USING GAMES TO IMPROVE FOREIGN LANGUAGE LEARNERS’ LANGUAGE SKILLS AND TEACHER’S ATTITUDE TOWARDS USING GAMES AS AN EDUCATIONAL TOOL - Akmaljonova, Makhliyo (Educational Research in Universal Sciences, 2023)
This study aims to find out the role of games in promoting students’ language skills and their teachers’ attitude toward it. In order to collect the data, the researchers employed a 25-item tests which was given to 20 English as a Foreign Language (EFL) learners in. Then, the students of 48th school in Namangan who were randomly divided into two groups of 10 learners functioning as control and experimental groups. The students in the experimental group received games in their language lessons and classes, while control group learners did not. At the end of the term, the same questionnaire was given to the students to know if playing games had a significant impact on their education. In addition, the teachers were asked to answer a online survey to investigate their attitudes toward playing games in language classes. The results showed that most of the teachers in this study believe that games have a positive influence on the students’ attitudes towards learning English and that using them in class serves many educational purposes. In addition, games played a significant role in improving the EFL leaners’ willingness to communicate. In the light of these findings, the researchers suggested using games as energizers and practical activities at the end of class not only to improve enthusiasm for learning, but also to improve the learners’ language skills.